Nutritional and biomass evaluation of a Megathyrsus maximus collection in a dry tropical climate in Colombia - Carvajal-Tapia, Juliana I.; Barahona-Rosales, Rolando; Castro-Montoya, Joaquín; Arango, Jacobo; Vivas Quila, Nelson J. (International Center for Tropical Agriculture, 2023)
Agronomic and nutritional parameters of a set of 28 accessions of Megathyrsus maximus established in Colombia during the rainy season were evaluated to identify accessions with differences in nutritional quality and characterize germplasm of M. maximus. ANOVA and multivariate analysis showed differences among accessions. Agronomic variables such as plant height, dry matter yield and green fresh weight were not correlated with nutritional variables. Flowering affected nutritional quality (neutral detergent fiber, acid detergent fiber and relative feed value). Flowering, fiber content, digestibility and crude protein content had the most influence on forage quality of M. maximus. The integral evaluation of biomass and nutritional parameters showed that the set of 28 M. maximus accessions contained 2 accessions with high nutritional quality and competitive biomass production. Heterogeneity of the collection in nutritional and agronomic assessments supports plant-breeding and offers alternatives for cattle producers in the tropics.